EFFECTIVENESS OF SUPRAMOLECULAR ANTHELMINTIC COMPLEXES APPLIED UNDER WORKING CONDITIONS FOR TREATMENT OF GASTROINTESTINAL STRONGYLATOSIS IN SHEEP - A. I. Varlamova; V. A. Dolgoshev; K. M. Sadov; E. E. Belova; I. I. Glamazdin; S. S. Halikov; Yu. S. Chistyachenko; A. V. Dushkin; S. D. Durdusov; I. A. Arkhipov (Российский паразитологический журнал, 2016)
Effectiveness of a supramolecular nanotech-based Albendazole – Fenbendazole complex has been tested using the Drug Delivery System. Tests for efficacy of new drugs Albendazole and Fenbendazole were conducted on 37 sheep spontaneously infected with Nematodirus sp. and other gastrointestinal strongylates in agricultural farm «Leninsky Put’» located in Pestravsky district of Samara region. The supra-molecular Albendazole – Arabinogalactan complex at a dose of 1,0 mg/kg of active ingredient and the base Albendazole at a dose of 10 mg/kg have shown a 100 % effectiveness. Albendazole – Chitosan complex has shown a 87,5 % extenseffectiveness and a 98,4 % reduction in number of nematode eggs in feces. The effectiveness of supramolecular Fenbendazole – polymer complex was lower.